Efektifitas Sistem Keuangan Syariah Terhadap Pertumbuhan Ekonomi Nasional - Rusda Diana; Haeriah Haeriah; Ifan Hidayat (Indo Publishing, 2026)
This study aims to examine the effectiveness of the Islamic financial system in promoting national economic growth. The research adopts a qualitative approach using a literature review method by analyzing various academic journals, books, and relevant sources. The findings indicate that the Islamic financial system plays a strategic role in supporting economic development through its fundamental principles, including risk-sharing, the prohibition of riba (interest), and the strengthening of real sector-based activities. Islamic financial instruments such as Islamic banking, sukuk, and zakat contribute to financial stability, investment growth, and a more equitable income distribution. However, several challenges remain, including low public literacy, limited market share, regulatory constraints, and lack of product innovation. Therefore, strategic efforts are needed, such as strengthening institutions, enhancing financial inclusion, and increasing public awareness. The development of a more adaptive and sustainable Islamic financial system is essential to support inclusive national economic growth.